Peroxydisulfate Activation by Carbon Materials for the Degradation of the Herbicide Ametryn in Waters - Graça, Cátia Alexandra Leça; Freitas, Gabriela de Souza [UNESP]; Soares, Olívia Salomé Gonçalves Pinto; Parizi, Marcela Prado Silva [UNESP] (American Chemical Society (ACS), 2024)
Brazil, the largest global sugar cane producer, utilizes approximately 10 million hectares for cultivation. However, the increased use of agrochemicals in this industry raises concerns about environmental and human health impacts. Inclusively, ametryn (AMT), a pesticide intensively used in sugar cane plantations, has been detected in several water matrices at concerning levels, which evidences the urgent need for the development of technologies capable of removing this pesticide from the environment. This study investigated the removal efficiency of AMT from aquatic environments via oxidation promoted by persulfate (PS) activation mediated by carbon-based materials, such as graphene, carbon nanotubes, and activated carbon. Granular activated carbon (GAC) emerged as the most suitable material due to its clear catalytic role. A central composite design was used to evaluate and optimize the factors influencing AMT degradation and mineralization, revealing that the initial PS concentration and GAC dosage strongly impact the degradation rate and organic carbon removal in different directions. GAC was submitted to surface functionalization with N- and O-precursors to investigate how this impacts PS activation, and positive enhancements were noted with the latter, with a mineralization degree 9% superior. Experiments with real water matrices evidence the impact of other water constituents on the degradation rate of the target pollutant (k′300), which was reduced by half when performed in groundwater. Notwithstanding, the system still demonstrated a consistent capacity to remove organic content, ranging from 60 to 50% TOCremoval, regardless of the water matrix, indicating that the system might be effective in real contamination scenarios. This research highlights the potential of GAC and its modified version for remediation of AMT-contaminated water remediation.